HUBUNGAN TINGKAT STRES DENGAN KESEJAHTERAAN PSIKOLOGIS PADA ANGGOTA KSBSI YANG MENGALAMI PHK - Jorgi Excellency Mboeik; Mernon Y. C. Mage; Marleny P. Panis (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Regional economic uncertainty and the intense social pressure following the loss of formal employment are the background to this research. These operational issues have triggered increased mental vulnerability and a drastic decline in workers' life satisfaction. The main focus of this scientific study is to analyze and empirically test the relationship between stress levels and the psychological well-being of members of the All-Indonesian Trade Union Confederation (KSBSI) who have experienced layoffs. This quantitative, descriptive, correlational research path was implemented using a questionnaire, reaching a sample of 137 respondents through a simple random sampling technique. Primary data measurement used the Depression Anxiety Stress Scale-42 and the Ryff Psychological Well-Being Scale, which were then statistically executed through residual normality tests and Pearson correlation analysis. The quantitative data empirically revealed a weak, significant negative correlation between stress levels and psychological well-being, with a correlation coefficient value of r of minus 0.193 at a significance parameter of p less than 0.001. The majority of research subjects were stably distributed in the moderate stress and moderate well-being categories. The main conclusion confirms that the escalation of workers' psychological stress is directly proportional to the decline in autonomy and self-acceptance. Employment organization practitioners are recommended to design coping management and psychosocial support drafts consistently. ABSTRAK Ketidakpastian ekonomi regional serta besarnya tekanan sosial pasca kehilangan pekerjaan formal melatarbelakangi kegiatan penelitian ini. Masalah operasional tersebut memicu peningkatan kerentanan mental serta penurunan drastis pada derajat kepuasan hidup para buruh. Fokus utama kajian ilmiah ini adalah membedah dan menguji secara empiris hubungan antara tingkat stres dan kesejahteraan psikologis anggota Konfederasi Serikat Buruh Seluruh Indonesia (KSBSI) yang mengalami pemutusan hubungan kerja. Langkah-langkah jalur riset kuantitatif deskriptif korelasional ini dioperasikan menggunakan kuesioner dengan menjangkau sampel sebanyak 137 responden melalui teknik simple random sampling. Pengukuran data primer menggunakan instrumen Depression Anxiety Stress Scale-42 dan Ryff Psychological Well-Being Scale, yang selanjutnya dieksekusi statistik lewat uji normalitas residual serta analisis korelasi Pearson. Data kuantitatif secara empiris menyingkap korelasi negatif lemah yang signifikan antara tingkat stres dan kesejahteraan psikologis dengan nilai koefisien korelasi r sebesar minus 0,193 pada parameter signifikansi p kurang dari 0,001. Mayoritas subjek penelitian terdistribusi secara stabil pada kategori tingkat stres sedang dan tingkat kesejahteraan sedang. Simpulan utama menegaskan bahwa eskalasi ketegangan psikologis buruh berbanding lurus dengan penurunan fungsi otonomi serta penerimaan diri. Praktisi organisasi ketenagakerjaan direkomendasikan merancang draf manajemen koping dan dukungan psikososial secara konsisten.